Malaria—Case Management in Lagos, Nigeria, With SD–BIOLINE HRP-2–Based RDTS. (21st September 2018) - Sanyaolu, Adekunle; Oyibo, Wellington; Olaniyan, Kayode; Orish, Verner; Iriemenam, Nnaemeka
Abstract: Objectives: This study was carried out to evaluate the performance characteristics of SD Bioline HRP-2 RDT in malaria case management using microscopy as a gold standard among patients at a primary health care center in Lagos, Nigeria. Methods: Study comprised 1, 276 consenting patients who were randomly selected from the outpatient department of a primary health center in the community. Venous blood samples of patients were collected and screened for malaria parasite infection using microscopy and SD Bioline HRP-2 RDT diagnostic methods. An analysis was performed to determine the sensitivity, specificity, positive predictive value, and negative predictive value of the SD Bioline HRP-2 RDT. Patients were administered with a case report form. Results: Among 1, 276 patients recruited for the study, only 197 (15.4%) and 186 (14.6%) were positive for P falciparum by HRP-2 RDT and microscopy ( P > .05). The sensitivity, specificity, positive predictive value, and negative predictive values were 94%, 98.5%, 91.4%, and 98.2%, respectively. Using RDT to correlate symptoms, afebrile fever recorded the highest in all age groups (810, 63%), while febrile fever with temperature ≥37°C recorded 229 (17.9%) in all age groups; 45.8% (584) of the patients had access to medication. Conclusion: SD Bioline HRP-2 RDT is reliable for parasite-based diagnosis of malaria infection but unreliable for correlating symptoms of malaria, especially fever with parasite identification.